Group Yoga Effects on Cancer Patient and Caregiver Symptom Distress: Assessment of Self-reported Symptoms at a Comprehensive Cancer Center. (December 2018) - Lopez, Gabriel; Chaoul, Alejandro; Powers-James, Catherine; Eddy, Carol A; Mallaiah, Smitha; Gomez, Telma I.; Williams, Janet L; Wei, Qi; Bruera, Eduardo; Cohen, Lorenzo
Background. Complementary and integrative health approaches such as yoga provide support for psychosocial health. We explored the effects of group-based yoga classes offered through an integrative medicine center at a comprehensive cancer center. Methods. Patients and caregivers had access to two yoga group classes: a lower intensity (YLow) or higher intensity (YHigh) class. Participants completed the Edmonton Symptom Assessment System (ESAS; scale 0-10, 10 most severe) immediately before and after the class. ESAS subscales analyzed included global (GDS; score 0-90), physical (PHS; 0-60), and psychological distress (PSS; 0-20). Data were analyzed examining pre-yoga and post-yoga symptom scores using paired t-tests and between types of classes using ANOVAs. Results. From July 18, 2016, to August 8, 2017, 282 unique participants (205 patients, 77 caregivers; 85% female; ages 20-79 years) attended one or more yoga groups (mean 2.3). For all participants, we observed clinically significant reduction/improvement in GDS, PHS, and PSS scores and in symptoms (ESAS decrease ≥1; means) of anxiety, fatigue, well-being, depression, appetite, drowsiness, and sleep. Clinically significant improvement for both patients and caregivers was observed for anxiety, depression, fatigue, well-being, and all ESAS subscales. Comparing yoga groups, YLow contributed to greater improvement in sleep versus YHigh (−1.33 vs −0.50, P = .054). Improvement in fatigue for YLow was the greatest mean change (YLow −2.12). Conclusion. A single yoga group class resulted in clinically meaningful improvement of multiple self-reported symptoms. Further research is needed to better understand how yoga class content, intensity, and duration can affect outcomes.